You are on page 1of 11

Actual Formula

Test #1

2

2

2

2

(a + b)(a – ab + b )
(a – b)(a + ab + b )
x= – b ±

2

b – 4ac
2a

2

y=

2

2

r –x
0
1
2
1
2

1
3
2
1
2
1
2

3
2

3

3

3

3

a +b =
a –b =

Test for even
functions

f( – x) = – f(x)
2

Formula

Quadratic Formula

f(x) = f( – x)

(x – h) + (y – k) = r

Test #2

2

Test for odd
functions
General equation
of a circle
Equation of a
semi-circle
lim 1 =
x → ∞ x
π 
sin   =
4 
π 
cos   =
4 
π 
tan   =
4 
π 
sin   =
3 
π 
sin   =
6 
π 
cos   =
3 
π 
cos   =
6 

π tan  3 π tan  6 3 1 3 sinθ cosθ cosθ sinθ tan θ = cotθ = 2 2 sin θ + cos θ = 1 2 2 1 + cot θ = cosec θ 2 2   =    =  2 Other trig identity tan θ + 1 = sec θ Other trig identity sinA = sinB a b Sine rule 2 2 a = b + c – 2bccosA 2 2 cosA = b + c – a 2bc 2 A = 1 ab sinC 2 Cosine rule for side Cosine rule for an angle Area of a triangle using trig cosx cosy + sinx siny cos(x – y) = cosx cosy – sinx siny cos(x + y) = sinx cosy + cosx siny sin(x + y) = sinx cosy – cosx siny sin(x – y) = tanx + tany 1 – tanx tany tan(x + y) = .

tanx – tany 1 + tanx tany tan(x – y) = 2sinx cosx sin 2x = 2 2 cos x – sin x 2 cos 2x = 1 – 2sin x 2 2cos x – 1 2tanx 2 1 – tan x tan 2x = tan  θ  2  Ratios: 2t 1–t 1–t 1 +t 2t 1 +t tan θ = 2 2 2 cosθ = 2 sinθ = rsin( θ + α ) asinθ + bcosθ = rsin( θ – α ) asinθ – bcosθ = rcos( θ – α ) acosθ + bsinθ = rcos( θ + α ) acosθ – bsinθ = 2 2 r= a +b tan α = b a Where r = and α = .

y1 + y2  2   2 m = y2 – y1 x2 – x1 Distance formula Midpoint Formula Gradient Formula m = tan θ Gradient using trig y – y1 = m(x – x1) Point-gradient formula y – y1 = y2 – y1 x – x1 x2 – x1 Two-point formula m1 = m2 Parallel lines proof m1m2 = -1 Perpendicular lines proof d = |ax1 + by1 + c| 2 2 a +b   tan θ =  m1 – m2   1 + m1m2  mx x = 2 + nx1 m+n y = my2 + ny1 m+n Perpendicular distance formula Angle between two lines Dividing interval in ratio m:n .General solution for sine General solution for cosine General solution for tan n θ = π × n + (-1) α θ = 2π × n ± α θ = π × n+α Graphs d = 2 2 (x2 – x1) + (y 2 – y 1)   P =  x1 + x2 .

0) 2 (x – h ) = 4a(y – k) (h . Focus Vertex Parametric form of: 2 x = 4ay . k) (h . Focus Vertex General equation of parabola.dy = dx lim f(x + h) – f(x) h → 0 h n –1 nx f'(x)n [f(x)] n–1 vu' + uv' vu' – uv' First principle differentiation d xn dx d [ f(x)] n = dx d uv dx 2 v d u dx v x = – b 2a Axis of symmetry in quadratic 2 The discriminant ∆ = b – 4ac –b a c a –d a e a Sum of roots 2 x = 4ay (0. k + a ) x = 2at y = at 2 Sum of roots two at a time Sum of roots three at a time Sum of roots four at a time Equation of basic parabola. a) (0.

Tn = a + (n – 1)d Term of an arithmetic series Sn = n (a + l) 2 n Sn = [ 2a + (n – 1)d] 2 Sum of an arithmetic series S = (n – 2) × 180° Sum of interior angles of an nsided polygon A = lb Area of rectangle 2 Area of a square bh Area of a triangle A = x 1 2 A = A = bh A = Area of a parallelogram 1 2 xy Area of rhombus 1 2 h(a + b) Area of trapezium 2 Area of circle A = πr S = 2(lb + bh + lh) V = lbh 2 S = 6x 3 Surface area of a rectangular prism Volume of a rectangular prism Surface area of a cube V = x Volume of a cube 2 Surface area of a cylinder S = 2π r + 2π r h .

2 V = πr h S = 4π r πr 4 3 V = 2 3 2 S = π r + π rl V = 1 3 2 πr h n+1 x +c n +1 h [ (y + y ) + 2(y + y + ... + y )] 0 n 1 2 n–1 2 where h = b – a n h [ (y + y ) + 4(y + y ) + 2(y + y )] 0 1 3 2 4 n 3 where h = b – a n n+1 (ax + b) +c a(n + 1) ⌠ 2 V = π  y dx ⌡ ⌠ 2 V = π  x dy ⌡ x e f(x) f'(x) e x e + c Volume of a cylinder Surface area of a sphere Volume of a sphere Surface area of a cone Volume of a cone ⌠ n  x dx ⌡ Trapezoidal rule Simpson’s Rule n ⌠  (ax + b) dx ⌡ Volume about the x-axis Volume about the y-axis d ex dx d e f(x) dx ⌠ x  e dx ⌡ .

1 eax + b + c a ⌠ ax + b  e dx ⌡ loga x + log a y log a (xy) loga x – log a y   loga  x  y  n loga x loga x loga x = log e x log e a 1 x f'(x) f(x) Change of base rule d log x e dx d log f(x) e dx ⌠ 1  dx ⌡ x ⌠ f'(x)  dx ⌡ f(x) log e x + c loge f(x) + c 180° π radians = C = 2πr Circumference of a circle l = rθ Length of an arc A = A = n 1 2θ r 2 1 2 θ r ( 2 – sinθ) sinx ≈ x tanx ≈ x cosx ≈ 1 Area of a sector Area of a minor segment Small Angles .

2 x = –n x d sin [ f(x)] dx d cos [ f(x)] dx d tan f(x) dx Complex growth and decay Special result for acceleration Displacement for SHM Acceleration for SHM .f'(x) cos [f(x)] – f'(x) sin [f(x)] 2 f'(x) sec f(x) 1 sin(ax + b) + c a – 1 cos(ax + b) + c a 1 tan(ax + b) + c a 1 2 x + 1 sin 2ax + c 4a 1 2 x – 1 sin 2ax + c 4a kQ kt ⌠  cos(ax + b) dx ⌡ ⌠  sin(ax + b) dx ⌡ 2 ⌠  sec (ax + b) dx ⌡ 2 ⌠  cos ax dx ⌡ 2 ⌠  sin ax dx ⌡ Exponential Growth & Decay dQ = dt Quantity Q = Ae dN = k(N – P) dt kt N = P + Ae 2 a = d  12 v   dx  x = a cos(nt + ∈) ..

y = Vsinθ . x = 0 . x = Vcosθ .2 a Amplitude of SHM 2π n Period of SHM 2 2 2 Velocity of SHM v = n (a – x ) . y = –g Initial Velocity of projectile Acceleration of a projectile x = Vt cosθ 2 y = Vt sinθ – gt 2 2 y = – gx 2 2 (1 + tan θ) + xtan θ 2V t = 2V sinθ g Horizontal displacement Vertical displacement Cartesian equation of motion Time of flight 2 θ x = V sin 2 g Range 2 x = V g 2 Max Range 2 θ h = V sin 2g -1 -1 f [f(x)] = f[f (x)] = x -1 – sin x -1 π – cos x Greatest height Proof for mutually inverse functions -1 sin ( – x) = -1 cos ( – x) = .

(n – 1)! n Pr = Arrangements where some are alike Arrangements in a circle ...-1 -1 – tan x tan ( – x) = π 2 sin x + cos x = -1 r = T2 T1 Tn = ar n–1 -1 Common ratio in geometric series Term of a geometric series n Sn = a(r – 1) for |r| > 1 r –1 n Sum of a geometric series  n A = P 1 + r  100     If f  a + b  = 0 2   a1 = a – f(a) f'(a) n –k +1 × b k a Sum to infinity of a geometric series Compound interest formula Halving the interval method Newton’s method of approximation TK + 1 = TK Sn = a(1 – r ) for |r| < 1 1–r S∞ = a 1–r n! (n – r)! n! s! t! .

Related Interests